South China, East Vietnam or West Philippine? comparative framing analysis of regional news coverage of Southeast Asian sea disputes - Freeman, Bradley C. (2017)
For years, the world paid scant attention to the sporadic skirmishes and sovereignty squabbles in what is known by many as the South China Sea. However, in the past few years, there have been several noteworthy happenings that have drawn the attention of media outlets, including a Chinese oil rig placement near Vietnam, a Philippine international court case, a U.S.–ASEAN summit, and Chinese reclamation projects.Many of the countries involved are members of the regional grouping known as ASEAN (Association of Southeast Asian Nations).This study examined Asean’s English-language press, looking at the amount, patterns, and tone of coverage given to regional maritime disputes.Results indicate that use of the term ‘South China Sea’ prevails in all countries except Vietnam.The Asean newspapers have devoted a consistent and substantial amount of space to covering the topic.Indonesia’s Jakarta Post tended to use neutral or positive language when mentioning Asean and the US, while China saw more negative associations in the coverage.Further research is suggested, taking into account mass communication theories and perspectives.